Another Baltic Postcolonialism: Young Latvians, Baltic Germans, and the emergence of Latvian National Movement. Issue 1 (20th November 2018) - Ijabs, Ivars
Abstract : This article looks at the emergence of Latvian nationalism in the mid-nineteenth century from the intercultural perspective of postcolonial theory. The writings of early Young Latvians, and the reaction to them from the dominant Baltic German elite, show that the emergence of a modern Latvian nationalism is to a large extent due to postcolonial mimicry, as described by Homi Bhabha. Attempts to imitate German cultural models and to develop a Latvian high culture lead to hostile reactions from the German side, which, in their turn, lead to increasing consolidation of Latvian nationalism. Since the Baltic German elite increasingly legitimized its rule in terms of cultural superiority, the Young Latvians' alliance with the Russian Slavophiles led it to treat the Latvian nationalists as culturally inferior and partly Asiatic, like the Russians.